Identification of PDHX as a metabolic target for esophageal squamous cell carcinoma. Issue 7 (24th May 2021) - Inoue, Jun; Kishikawa, Masahiro; Tsuda, Hitoshi; Nakajima, Yasuaki; Asakage, Takahiro; Inazawa, Johji
Abstract: The metabolism in tumors is reprogrammed to meet its energetic and substrate demands. However, this metabolic reprogramming creates metabolic vulnerabilities, providing new opportunities for cancer therapy. Metabolic vulnerability as a therapeutic target in esophageal squamous cell carcinoma (ESCC) has not been adequately clarified. Here, we identified pyruvate dehydrogenase (PDH) component X ( PDHX ) as a metabolically essential gene for the cell growth of ESCC. PDHX expression was required for the maintenance of PDH activity and the production of ATP, and its knockdown inhibited the proliferation of cancer stem cells (CSCs) and in vivo tumor growth. PDHX was concurrently upregulated with the CD44 gene, a marker of CSCs, by co‐amplification at 11p13 in ESCC tumors and these genes coordinately functioned in cancer stemness. Furthermore, CPI‐613, a PDH inhibitor, inhibited the proliferation of CSCs in vitro and the growth of ESCC xenograft tumors in vivo. Thus, our study provides new insights related to the development of novel therapeutic strategies for ESCC by targeting the PDH complex‐associated metabolic vulnerability. Abstract : Inoue et al. found that pyruvate dehydrogenase (PDH) component X expression is necessary for PDH activity and is involved in the cancer stemness of esophageal squamous cell carcinoma (ESCC) cells, thereby being metabolically essential for the tumor growth of ESCC. This study provides new insights related to the development of novel therapeutic strategies for ESCC by targeting the PDH complex‐associated metabolic vulnerability.